Models for calculating the integral quality indicator of the offset printing process for the IIOT-system - REPETA, Vyacheslav; RYVAK, Pavlo; KRYKHOVETS, Oleksandra (Applied Computer Science, 2026)
The paper is devoted to the problem of comprehensive quality assessment in offset printing. On the basis of the research conducted, the quality indicators of sheet-fed offset printing with dampening are determined, namely, the print color difference, the fine line width, the color combination accuracy, the “gray balance” and the dot gain. These indicators were divided into two groups: the first group reflects the color reproduction, while the second concerns the reproduction of fine image elements. Based on the principles of fuzzy logic, the evaluation terms “low”, “medium”, “high” are assigned to the print quality, and a fuzzy knowledge base of the print quality parameters with the fulfillment of the “if-then” condition is formed. Fuzzy logic equations for the calculation of print quality options are constructed, and the defuzzification operation carried out using the “center of gravity” method allows to obtain a quantitative print quality indicator as a result of observing the corresponding modes of the offset printing technological process. The values of the indicators of the parameters of the offset printing quality obtained according to the results of the control and the calculation of the integral indicator serve as data for the reporting of the process in the Industrial Internet of Things system.